2011
DOI: 10.5755/j01.ee.22.3.516
|View full text |Cite
|
Sign up to set email alerts
|

Multi-attribute Decision-making in Economics of Fire Protection

Abstract: The economic decisions concerning fire safety of built property may involve alternative solutions (alternatives) of fire protection measures, comparison of buildings with different fire safety levels, choice among construction products with different properties of performance in fire. The need to choose among alternatives may be faced by various interested parties: fire safety regulators (authorities on national level), insurers, architects (building designers), manufacturers of fire protection measures, prope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…Practical procedures for ranking and weighting the zones can be borrowed in the field of multiple criteria decision making (MCDM). For instance, the weights p k can be specified by organising an expert panel and utilising expert opinions by means of a well-known MCDM method called AHP (e.g., Luria, Aspinall 2003;Turskis, Zavadskas 2010;Vaidogas, Šakėnaitė 2010Vaidogas, Šakėnaitė , 2011.…”
Section: Disaggregation Of Road Segmentmentioning
confidence: 99%
“…Practical procedures for ranking and weighting the zones can be borrowed in the field of multiple criteria decision making (MCDM). For instance, the weights p k can be specified by organising an expert panel and utilising expert opinions by means of a well-known MCDM method called AHP (e.g., Luria, Aspinall 2003;Turskis, Zavadskas 2010;Vaidogas, Šakėnaitė 2010Vaidogas, Šakėnaitė , 2011.…”
Section: Disaggregation Of Road Segmentmentioning
confidence: 99%
“…It is worth noting that fuzzy decision-making theory has some advantages to cope with uncertain information. Since Zadeh (1965) first introduced fuzzy set theory, decision making based on fuzzy sets has been successfully applied in many fields, such as recommender system (Tejeda-Lorente et al, 2014;Martínez-Cruz et al, 2015;Yager, 2003Yager, , 2004, education (Bryson and Mobolurin, 1995), medical care (James and Dolan, 2010), engineering (Chen and Weng, 2006;Lennon et al, 2013;, economics (Ölçer et al, 2006;Vaidogas and Sakenaite, 2011;Meng et al, , 2016d, reservoir flood control (Fu, 2008), facility location selection (Kahraman et al, 2003), new product development (NDP) project screening (Meng and Chen, 2017a), and supplier selection . With the increasing complexity of the decision-making problems, researchers found that it is insufficient to address decision-making problems by using fuzzy sets, which only permit the decision maker to apply one fuzzy number to denote the uncertainty.…”
Section: Introductionmentioning
confidence: 99%
“…Multi-attribute decision making (MADM) has been deeply studied and widely applied in many fields, such as education (Bryson and Mobolurin, 1997), medical care (James and Dolan, 2010), military (Robert and Swezey, 1979), engineering (Lennon et al, 2013), social sciences (Cavus, 2011) and economics (Vaidogas and Sakenaite, 2011;Zeng and Chen, 2015;. Because of the complexity and uncertainty of multi-attribute decision-making problems, it is impractical to use exact number to evaluate the attribute, so Zadeh (1965Zadeh ( , 1973 proposed (type-2) fuzzy set, Atanassov (1986), Atanassov and Gargov (1989) introduced (interval-valued) intuitionistic fuzzy sets, and (interval-valued) hesitant fuzzy sets (Rodriguez et al, 2014a(Rodriguez et al, , 2014bMu et al, 2015;Chen et al, 2013) are defined.…”
Section: Introductionmentioning
confidence: 99%